Face-To-Face Double-Lumen Tube Intubation With the Airtraq Video Laryngoscope for Emergency Thoracic Surgery: A Case Report. (March 2022) - Ynineb, Yacine; Boglietto, Emilie; Bonnet, Francis; Quesnel, Christophe; Garnier, Marc
Double-lumen intubation is commonly used for thoracic surgery as it allows rapid and effective one-lung ventilation. However, it is more difficult than single-lumen tube intubation, notably in the context of emergency surgery and/or in hypoxemic patients. We report the case of a 57-year-old patient requiring emergency revision surgery after an upper right lobectomy due to postoperative pneumothorax and pleuropneumonia. As rapid lung isolation was required due to a bronchopleural fistula, rapid sequence induction and double-lumen tube intubation were performed. In addition, as the patient was hypoxemic with incomplete pre-oxygenation and too uncomfortable to tolerate the recumbent position despite high-flow oxygen, intubation was performed in face-to-face position. The patient was successfully intubated in 22 seconds and the right lung immediately isolated, allowing the surgeon to clean the pleural cavity. This is the first report of a double-lumen tube intubation in face-to-face position. The expected difficulties related to this type of intubation were successfully prevented using an Airtraq laryngoscope. Although such a strategy cannot be recommended from this one case, this report is encouraging for future studies evaluating the potential advantages of Airtraq use for double-lumen face-to-face intubation for emergency thoracic surgery.